(untitled) (The Research of Medical Science Review, 2025)
Objective: To study the effect of DRIL on visual acuity of diabetic macular edema patients on standard treatment with Anti-Vascular Endothelial Growth Factors in terms of mean change in Best-Corrected Visual Acuity after treatment of DRIL. Methods: In this study, we included 66 patients with a diagnosis of DRIL due to DME having aged 18-70 years. The study was conducted from 31 July 2024 to 30 January 2025. The assessment of Best-Corrected Visual Acuity (BCVA) for each participant was conducted by the researcher using Snellen's Chart. Following the initial treatment, patients received an intravitreal injection of Bevacizumab at a dose of 1.25 mg. A month later, a follow-up assessment was conducted to evaluate the changes in best-corrected visual acuity (BCVA). Additionally, the presence of disruption of the inner retinal layers (DRIL) was assessed using optical coherence tomography (OCT). All findings were systematically documented. Results: The average age of participants was found to be 58.7±8.9 years. Among the 66 participants, 35 individuals, accounting for 53%, were male. At baseline, the Best Corrected Visual Acuity (BCVA) was measured at 0.68±0.31. After one month, the BCVA was observed to be 0.55±0.28. This resulted in a mean change in BCVA of 0.13±0.29, indicating a notable shift in visual acuity over the observed period. Conclusion: Treatment of DRIL is associated with significant improvements in BCVA in diabetic macular edema (DME) patients. All patients of DME with reduced vision should be evaluated for the presence of DRIL, as treating the DRIL can improve visual acuity in these patients.